2022
DOI: 10.3389/fpls.2022.1014266
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and functional analysis of non-specific lipid transfer protein family genes in sugarcane under Xanthomonas albilineans infection and salicylic acid treatment

Abstract: Plant non-specific lipid transfer proteins (nsLTPs) are small basic proteins that play a significant regulatory role in a wide range of physiological processes. To date, no genome-wide survey and expression analysis of this gene family in sugarcane has been performed. In this study we identified the nsLTP gene family in Saccharum spontaneum and carried out expression profiling of nsLTPs in two sugarcane cultivars (Saccharum spp.) that have different resistance to leaf scald caused by Xanthomonas albilineans (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Notably, the results of the current study are in line with those of recent studies, which demonstrated that gene duplication for acquiring new genes in this family genes was a common occurrence in sugarcane [ 26 , 27 , 28 ]. Due to the complex polyploid nature of sugarcane, functional divergence and redundancy is more frequent, and the unique retention profile of duplicated genes after the establishment of polyploidy might explain a general increase in biological complexity [ 29 ]. In addition to duplication events, the influence of polyploidy on mutation rates might also cause insertion–deletion events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results of the current study are in line with those of recent studies, which demonstrated that gene duplication for acquiring new genes in this family genes was a common occurrence in sugarcane [ 26 , 27 , 28 ]. Due to the complex polyploid nature of sugarcane, functional divergence and redundancy is more frequent, and the unique retention profile of duplicated genes after the establishment of polyploidy might explain a general increase in biological complexity [ 29 ]. In addition to duplication events, the influence of polyploidy on mutation rates might also cause insertion–deletion events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that some genes shared similar expression profiles, but some genes had different expression profiles under either Aaa or Xa infection, suggesting that sugarcane ARF family genes underwent functional divergence and redundancy in evolution. This phenomenon is frequent in plants, particularly in complex polyploidy crops such as sugarcane ( Li et al, 2022 ). Notably, some ARF genes (such as SpapARF02 ) showed similar functions in sugarcane defense responses to Aaa and Xa infections, while others (such as SpapARF01 ) played the opposite role in responses to both bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the nsLTP gene family has been reported in many plant species, such as poplar (Populus L.) [37], sugarcane (Saccharum spp.) [23], foxtail millet (Setaria italica L.) [20], and Chinese white pear (Pyrus bretschneideri) [38]. Studies on the nsLTP gene family in chestnut have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids, as an important secondary metabolite, play a crucial role in plants' response to environmental stress, such as membrane stabilization, plant extracellular vesicle function, and cuticle and cell wall integrity [13][14][15][16]. In plants, considerable evidence shows that nsLTPs are involved in a range of lipid-related biological processes, including oil accumulation, cuticular wax deposition, pollen wall formation, and cutin synthesis [13,[17][18][19], while nsLTPs have also been found to respond to a variety of abiotic/biotic stresses, such as drought, high salinity, heat, cold stress, pathogen defense, PEG 6000 stress, and IAA and ABA stresses [20][21][22][23][24][25]. For abiotic stress, OsLTPL159 increased cold tolerance at the early seedling stage in rice [26].…”
Section: Introductionmentioning
confidence: 99%